2010
DOI: 10.1002/pbc.22479
|View full text |Cite
|
Sign up to set email alerts
|

R1507, a fully human monoclonal antibody targeting IGF‐1R, is effective alone and in combination with rapamycin in inhibiting growth of osteosarcoma xenografts

Abstract: IGF-1R inhibition by R1507 induced tumor growth delays and improvement in event-free survival in four of six osteosarcoma xenograft tumor lines. R1507 negates increased signaling through AKT in response to mammalian target of rapamycin inhibition, suggesting that the combination is worthy of further evaluation in patients. As R1507 and other IGF-1R inhibitors advance in clinical trials, it will be important to understand biomarkers of response and pathways of resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 15 publications
2
55
1
Order By: Relevance
“…Several anti-IGFIR mAbs with in vitro and in vivo antitumor activities in sarcoma models have been developed (21)(22)(23)(24)(25). These mAbs inhibit IGFI and IGFII signaling through IGFIR and heterodimeric IGFIR/IR-A, but do not inhibit IGFII signaling through IR-A.…”
Section: Introductionmentioning
confidence: 99%
“…Several anti-IGFIR mAbs with in vitro and in vivo antitumor activities in sarcoma models have been developed (21)(22)(23)(24)(25). These mAbs inhibit IGFI and IGFII signaling through IGFIR and heterodimeric IGFIR/IR-A, but do not inhibit IGFII signaling through IR-A.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent expression of IGF-1R, IGF-1, and IGF-2 in osteosarcoma cell lines and patient samples has been reported (24,25). Blocking IGF-mediated growth in osteosarcoma can inhibit tumor growth and metastasis in murine osteosarcoma (5,26,27). In vivo study also demonstrated that tumor growth in xenografts can be inhibited with anti-IGF-1R antibody (5).…”
Section: Discussionmentioning
confidence: 91%
“…Blocking IGF-mediated growth in osteosarcoma can inhibit tumor growth and metastasis in murine osteosarcoma (5,26,27). In vivo study also demonstrated that tumor growth in xenografts can be inhibited with anti-IGF-1R antibody (5). In this study, we first used molecular modeling (Fig.5), and Western blot analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations